2016
DOI: 10.1007/s00464-016-4947-1
|View full text |Cite
|
Sign up to set email alerts
|

Treatment outcomes and recurrence following standard cold forceps polypectomy for diminutive polyps

Abstract: Although recurrence may develop after standard CFP of diminutive polyps, recurrence as advanced adenoma is rare. Large polyp size, right colon polyp, and endoscopist are risk factors for recurrence after standard CFP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 22 publications
0
8
1
Order By: Relevance
“…The recurrence rate of 2.1 % at 1 year following CFP is acceptably low compared with other polyp resection techniques, such as endoscopic mucosal resection, polypectomy, and hot biopsy [25]. The recurrence rate in the present study was also lower than the only published study that has reported local recurrence (cumulative recurrence rate of 17 % over 5 years) following CFP using standard forceps for diminutive polyps [20]. However, that study was retrospective in nature and the diagnosis of the majority of the recurrent lesions was not definitive.…”
Section: Discussioncontrasting
confidence: 53%
See 1 more Smart Citation
“…The recurrence rate of 2.1 % at 1 year following CFP is acceptably low compared with other polyp resection techniques, such as endoscopic mucosal resection, polypectomy, and hot biopsy [25]. The recurrence rate in the present study was also lower than the only published study that has reported local recurrence (cumulative recurrence rate of 17 % over 5 years) following CFP using standard forceps for diminutive polyps [20]. However, that study was retrospective in nature and the diagnosis of the majority of the recurrent lesions was not definitive.…”
Section: Discussioncontrasting
confidence: 53%
“…The combined use of jumbo forceps and NBI-magnified observation was able to achieve a low rate of local recurrence (mean 2.15 %, 95 %CI 1.4 % -3.2 %) in this study. There is a possibility that the local recurrence rates may exceed the acceptable limit of 5 % (as permitted by the American Society for Gastrointestinal Endoscopy guidelines) if CFP is performed without jumbo forceps and NBI-magnified observation [17,20]. We, therefore, recommend that jumbo forceps and NBI-magnified observation of the resection margin are utilized in CFP for diminutive polyps.…”
Section: Totalmentioning
confidence: 99%
“…In addition, some studies have shown that CP is useful for removing polyps of more than 10 mm in size [22-24]; however, some of those reports recommend piecemeal polypectomy. The reported rate of incomplete resection by CP was 3.9% [25] and there is a report of recurrence after CP [26]; thus, careful consideration for the indication of size is necessary.…”
Section: Discussionmentioning
confidence: 99%
“…[30] Lee et al reported that the rate of recurrence after CFP was 17% during a median follow-up period of 59.7 months (Interquartile range [IQR], 41.1–75.6 months) in a retrospective study, whereas it remains unknown about recurrence after CSP. [31] As such, the rate of recurrence after CSP should be evaluated in a prospective study.…”
Section: Discussionmentioning
confidence: 99%